Informal workplace practices and learning experiences of permanent and hourly-paid teachers: a comparative study - Güvercin, Gökçe. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2014., 2014)
This study was conducted to explore the influences of the changing teacher recruitment regulations on teachers’ daily experiences and practices, and the consequences of those influences on teachers’ informal workplace learning experiences. The study is focused on two teacher statuses as hourly-paid and permanent teachers. Theoretical sampling method was used. Biographical Narrative Interviews were conducted and then analyzed using the Documentary Method. In the analysis, different teacher orientation frameworks were constructed. Then, these orientations were abstracted and detached from the individual case with the means of sense-genetic typification. Next, the constructed types were put in a social context with socio-genetic typification. According to the elicited results, hourly-paid and permanent teachers who are the graduates of faculties of education or the holders of pedagogical formation certificate complete their teacher training period with a lack of required skills and background for teaching practices. After graduation, when they start teaching, hourly-paid and permanent teachers acquired experiences and practices that are distinctly varied in relation to their employment type. Permanent teachers made an effort to improve their teaching skills through experimenting, socialization environmental scanning with these informal learning experiences, permanent teachers gradually improved their professional competencies. On the contrary, hourly-paid teachers identify being a good teacher only with personal characteristics. They assume that they have a natural ability to teach. Neither do they critically reflect on their own professional experiences, nor do they prefer to observe more experienced teachers in the way that permanent teachers do. Furthermore, hourly-paid teachers, since they teach with the possibility of losing their jobs at any time, feel the need to prove how good they are at teaching. They compare their professional competencies with those of permanent teachers and highlight what they consider their own superiority.
Keywords: Teachers -- Legal status, laws, etc. -- Turkey.; Teachers -- Rating of -- Turkey.; Teachers -- Salaries, etc. -- Turkey.